Critical theory of AI - Lindgren, Simon (Cambridge, United Kingdom Polity Press, 2024)
We live in an age of artificial intelligence. Machines think and act in ever more complex ways, making suggestions and decisions on our behalf. While AI might be seen as practical and profitable, issues of data surveillance, algorithmic control, and sexist and racist bias persist. In this rapidly changing landscape, social analysis of AI risks getting scaled down to issues of 'ethics', 'responsibility', and 'fairness'. While these are important issues, they must be addressed not from an 'AI first' perspective, but more thoroughly in terms of power and contention. Approaching artificial intelligence from the often overlooked perspective of critical social theory, this book provides a much-needed intervention on how both old and new theories conceptualize the social consequences of AI. Questions are posed about the ideologies driving AI, the mythologies surrounding AI, and the complex relationship between AI and power. Simon Lindgren provides a way of defining AI as an object of social and political critique, and guides the reader through a set of contentious areas where AI and politics intersect. In relation to these topics, critical theories are drawn upon, both as an argument for and an illustration of how AI can be critiqued. Given the opportunities and challenges of AI, this book is a must-read for students and scholars in the humanities, social sciences, and STEM disciplines. -- Provided by publisher.
1. AI and critical theory -- 2. AI assemblage -- 3. Ideology behind AI -- 4. Ideology within AI -- 5. Social machines -- 6. AI at work -- 7. AI subjects -- 8. AI in the loop.
Includes bibliographical references (pages 171-201) and index.
Keywords: Artificial intelligence -- Philosophy; Intelligence artificielle -- Philosophie